National character is in literary images (on an example Kazakh and Chinese literatures) (Journal of Oriental Studies, 2016)
This article discusses the problem of creation of national character for example, Chinese and Kazakh literature, which is one of the key issues in the problem of correlation of national and international literature, in General, are examples of the Chinese and Kazakh scientists who have studied the characteristics of national character in fiction, the components of the national identity of the Kazakh and Chinese writers. Discusses problem of national fine art form, literary and historical traditions, realities, mores, customs, geographical features and so on .
Keywords: national character; category of characters